Mass analysis of charged aerosol particles in NLC and PMSE during the ECOMA/MASS campaign - Robertson, S.; Horányi, M.; Knappmiller, S.; Sternovsky, Z.; Holzworth, R.; Shimogawa, M.; Friedrich, M.; Torkar, K.; Gumbel, J.; Megner, L.; Baumgarten, G.; Latteck, R.; et al. (München : European Geopyhsical Union, 2009)
MASS (Mesospheric Aerosol Sampling Spectrometer) is a multichannel mass spectrometer for charged aerosol particles, which was flown from the Andøya Rocket Range, Norway, through NLC and PMSE on 3 August 2007 and through PMSE on 6 August 2007. The eight-channel analyzers provided for the first time simultaneous measurements of the charge density residing on aerosol particles in four mass ranges, corresponding to ice particles with radii <0.5 nm (including ions), 0.5–1 nm, 1–2 nm, and >3 nm (approximately). Positive and negative particles were recorded on separate channels. Faraday rotation measurements provided electron density and a means of checking charge density measurements made by the spectrometer. Additional complementary measurements were made by rocket-borne dust impact detectors, electric field booms, a photometer and ground-based radar and lidar. The MASS data from the first flight showed negative charge number densities of 1500–3000 cm−3 for particles with radii >3 nm from 83–88 km approximately coincident with PMSE observed by the ALWIN radar and NLC observed by the ALOMAR lidar. For particles in the 1–2 nm range, number densities of positive and negative charge were similar in magnitude (~2000 cm−3) and for smaller particles, 0.5–1 nm in radius, positive charge was dominant. The occurrence of positive charge on the aerosol particles of the smallest size and predominately negative charge on the particles of largest size suggests that nucleation occurs on positive condensation nuclei and is followed by collection of negative charge during subsequent growth to larger size. Faraday rotation measurements show a bite-out in electron density that increases the time for positive aerosol particles to be neutralized and charged negatively. The larger particles (>3 nm) are observed throughout the NLC region, 83–88 km, and the smaller particles are observed primarily at the high end of the range, 86–88 km. The second flight into PMSE alone at 84–88 km, found only small number densities (~500 cm−3) ...